STUDI PERBANDINGAN PERLINDUNGAN HUKUM DALAM TRANSAKSI TABUNGAN EMAS DIGITAL PLUANG DAN INDOGOLD: Studi Perbadingan Pada Aplikasi Pluang dan Indogold - Ulya, Widadatul; Afifah, Hana; Setyanugraha, R. Satria (UNPERBA, 2023)
The interest of the Indonesian people to save gold digitally is getting higher, amid the rise of illegal digital financial institutions. PT PG Berjangka sells Digital Gold Savings products through the Pluang, while PT Indogold Solusi Gadai through the Indogold. PT PG Futures has been registered with CoFTRA and the Futures Clearing House, but PT Indogold Solusi Gadai has not been registered with CoFTRA and also with the Futures Clearing House, even its registered status with the OJK is no longer valid and it is recommended to apply for a permit to the OJK under another work unit. Therefore, researchers are interested in conducting research on legal protection in digital gold savings transactions. This study uses an empirical juridical approach. From the results of the study, it was concluded that the laws and regulations in Indonesia had preventively provided legal protection in Pluang and Indogold digital gold saving transactions. However, Indogold consumers do not get the protection as referred to in the CoFTRA Regulation concerning Technical Provisions for the Implementation of the Digital Gold Physical Market on the Futures Exchange.